Modern instrumental approaches to modelling the commercial bank's financial investment policy - Serhiienko, Olena; Volosnikova, Nataliia; Kochorba, Valeriia; Yehorova, Yuliіa; Kolomiiets, Yuliya (Fintechalliance LLC, 2024)
The article considers a complex of modern analytical approaches to the systematic modelling of the commercial bank's financial investment policy based on international practice. The authors examine the key aspects of modelling and analytical technologies that determine the strategic decisions of banking institutions in the field of financial investment, in particular, taking into account global economic and financial trends. The article highlights model and methodological approaches and tools used to analyze and forecast market conditions, risks and profitability in the context of banks' financial investments. The research purpose is to expand the instrumental apparatus and prove the significance of the technology's role and the implementation of a wide range of methods and modern international approaches to modelling the commercial banks' financial investment policy in the direction of strategic development in the context of global megatrends. The research is based on the tools of models of spatial econometric analysis (panel data), adaptive forecasting of dynamic series, multivariate data analysis, cluster and discriminant analysis. The paper presents an aggregated instrumental basis for the main key directions, namely analysis of the bank's financial indicators; assessment of the stock market's business activity level; classification and grouping of economic objects according to the investment attractiveness level. The data of the studied area interact and complement each other, allowing us to comprehensively generalize and objectively present the fundamental basis for decision-making. As a result of these stages' implementation, we can determine the optimal financial investment strategies, which contribute to increasing the commercial banks' efficiency and stability in the modern conditions of globalization and financial instability. An analytical view of the study of international approaches makes the article relevant for specialists in the fields of finance, economics and banking.

У статті розглянутий комплекс сучасних аналітичних підходів до системного моделювання політики фінансового інвестування комерційного банку на основі міжнародної практики. Автори досліджують ключові аспекти моделювання й аналітичних технологій, що визначають стратегічні рішення банківських установ у царині фінансового інвестування, зокрема враховуючи глобальні економічні та фінансові тенденції. Стаття висвітлює модельно-методологічні підходи та методичні інструменти, які використовують для аналізу та прогнозування ринкових умов, ризиків і доходності в контексті фінансових інвестицій банків. Мета дослідження полягає в розширенні інструментального апарату, доведенні значущості ролі технологій та імплементації широкого спектра методів і сучасних міжнародних підходів до моделювання політики фінансового інвестування комерційних банків у напрямі стратегічного розвитку в контексті глобальних мегатрендів. Дослідження базується на інструментарії моделей просторового економетричного аналізу (панельні дані), адаптивного прогнозування динамічних рядів, багатовимірного аналізу даних, кластерного та дискримінантного аналізу. У роботі презентований агрегований інструментальний базис за основними ключовими напрямами, а саме: аналіз фінансових показників банку; оцінка рівня ділової активності фондового ринку; класифікації та угрупування економічних об’єктів за рівнем інвестиційної привабливості. Дані досліджуваної царини взаємодіють і доповнюють одне одного, дозволяючи комплексно узагальнити та об'єктивно представити фундаментальну базу для ухвалення рішень. Результати імплементації дозволять визначити оптимальні стратегії фінансового інвестування, які сприяють підвищенню ефективності й стійкості комерційних банків у сучасних умовах глобалізації та фінансової нестабільності. Аналітичний погляд на вивчення міжнародних підходів робить статтю актуальною для фахівців у царині фінансів, економіки та банківської справи.
Сучасні інструментальні підходи до моделювання політики фінансового інвестування комерційного банку
Keywords: commercial banks; financial sector; economic and mathematical modelling; investment analysis; correlation; models; stock market; forecasting; decision-making; комерційні банки; фінансовий сектор; економіко-математичне моделювання; інвестиційний аналіз; кореляція; прогнозування; ухвалення рішень